Middle East respiratory syndrome coronavirus in Al-Madinah City, Saudi Arabia: Demographic, clinical and survival data - Nahid Sherbini; Ayman Iskandrani; Ayman Kharaba; Ghalilah Khalid; Mohammed Abduljawad; Hamdan AL-Jahdali (Journal of Epidemiology and Global Health, 2019)
Background Middle East respiratory syndrome coronavirus (MERS-CoV), is an emerging virus respiratory infection. It has a high mortality rate and a wide spectrum of clinical features. This study describes the clinical characteristics and outcome of MERS infected patients. Methods A retrospective study was conducted of all confirmed MERS-CoV infections from March 2014 to May 2014 at two tertiary care hospitals in Al-Madinah region (Saudi Arabia). We gathered data about demographic, clinical presentation, and factors associated with severity and mortality. Results A total of 29 cases were identified; 20 males (69%) and nine females (31%), age 45 ± 12 years. The death rate was higher for men (52%) than for women (23%). Initial presentation was fever in 22 (75%) cases, cough in 20 (69%) cases, and shortness of breath in 20 (69%) cases. Associated comorbidities were diabetes mellitus in nine (31%) patients and chronic kidney disease (CKD) in eight (27%) patients. Duration of symptoms before hospitalization ranged from 2.9 days to 5 days. Elevated liver enzymes were present in 14 (50%) patients and impaired renal profile present in eight (27%) patients. We also describe in this study radiological patterns and factors associated with mortality. Conclusion MERS-CoV infection transmission continues to occur as clusters in healthcare facilities. The frequency of cases and deaths is higher among men than women and among patients with comorbidities.